2007
DOI: 10.1542/peds.2006-1498
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Diagnosed After 2 Months of Age Leads to Worse Outcomes and Requires More Therapy

Abstract: Newborn screening was associated with improved growth, reduced morbidity, and reduced therapy, yet generated equivalent pulmonary outcome compared with late clinical diagnosis, suggesting that newborn screening may slow cystic fibrosis lung disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 29 publications
3
86
1
2
Order By: Relevance
“…18 The literature suggests that subjects with CF diagnosed within 2 months of life are most likely to benefit from early interventions. 33 In California, 74.5% of CF NBS-positive newborns were seen by CFCs before age 2 months; this time frame was largely influenced by the 2 to 3 weeks needed to complete DNA sequencing. Improvements have been made to reduce this time by conducting both mutation panel and DNA sequence testing in the same physical location and in reducing assay testing time.…”
Section: Resultsmentioning
confidence: 99%
“…18 The literature suggests that subjects with CF diagnosed within 2 months of life are most likely to benefit from early interventions. 33 In California, 74.5% of CF NBS-positive newborns were seen by CFCs before age 2 months; this time frame was largely influenced by the 2 to 3 weeks needed to complete DNA sequencing. Improvements have been made to reduce this time by conducting both mutation panel and DNA sequence testing in the same physical location and in reducing assay testing time.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] We have also shown that for almost half of the population of our clinic, all of whom are black, recognition of CF is difficult, leading to late diagnosis and detrimental effects on disease progression. [15] There may be many reasons for this, including a high prevalence of poverty-associated conditions with similar presentation, i.e. protein energy malnutrition, HIV infection and tuberculosis, which affect the black population in SA to a considerable extent.…”
Section: Discussionmentioning
confidence: 99%
“…This increased risk was eventually linked to the lack of measures aiming to limit cross infections in that particular centre and subsequent studies failed to confirm it (Siret et al, 2003;Sims et al, 2005;Baussano et al, 2006;Collins et al, 2008). In countries with a high level of medical care, neonatal screening enables clinicians to diagnose CF in infants before the age of 2 months, with demonstrable benefits (Sims et al, 2007).…”
Section: Early Diagnosis: Cf Newborn Screening (Nbs)mentioning
confidence: 99%